2016
DOI: 10.15766/mep_2374-8265.10429
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Disability and Health for Preclinical Medical Students: Didactic and Disability Panel Discussion

Abstract: Introduction Millions of American patients have a disability, and their health care outcomes depend on the attitudes of their health care providers towards persons with disabilities. Overly negative health care provider attitudes lead to significant misunderstandings about what it means to have a disability, inappropriate assumptions, and poor care. However, very few medical schools teach about disability. Methods We developed a preclinical medical student curriculum th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
(10 reference statements)
1
17
0
Order By: Relevance
“…In particular, students would like further instruction on how to bring up the topic of disability with their patients when medically relevant. These findings echo those from the Rogers et al 8 session, which suggested that previous experience and training in working with individuals with disabilities are associated with better provider attitudes. 13 Further work should seek to equip students with effective tools as they move into clinical settings, as well as to reassess student comfort levels in those settings.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In particular, students would like further instruction on how to bring up the topic of disability with their patients when medically relevant. These findings echo those from the Rogers et al 8 session, which suggested that previous experience and training in working with individuals with disabilities are associated with better provider attitudes. 13 Further work should seek to equip students with effective tools as they move into clinical settings, as well as to reassess student comfort levels in those settings.…”
Section: Discussionsupporting
confidence: 81%
“…[10][11][12] Among these, "Introduction to Disability and Health for Preclinical Medical Students: Didactic and Disability Panel Discussion" by Rogers et al is a stand-alone disability session available in MedEdPORTAL that explores disability within a sociocultural context and harnesses shared student reflection so that students can understand and develop their own attitudes. 8 A systematic review of health care providers' attitudes toward people with disabilities conducted in 2012 concluded that attitudes were generally favorable, but that that some students and health care providers experienced "discomfort or anxiety when challenged with the responsibility of treating a person with physical disabilities." 13 These findings raise the question of whether low comfort level and limited familiarity with disability-more so than overt undervaluation of individuals with disability-may frequently underlie suboptimal care.…”
Section: Citationmentioning
confidence: 99%
“…Ten articles were identified that addressed interventions related to disabilities, a physical or mental impairment that limits the patient's daily activities. [127][128][129][130][131][132][133][134][135][136] Only one of the articles described a longitudinal intervention with three of the ten describing 1-hto 3-h-long programs. The articles emphasized the importance of experience interacting with people with disabilities and developing a greater understanding of the problems they face when accessing healthcare.…”
Section: Specific Populationsmentioning
confidence: 99%
“…For example, the Northern Ontario School of Medicine gathered the perspectives and suggestions of local aboriginal communities to inform curriculum interventions (Strasser & Marsh, 2014). Other medical schools have used patient narratives to inform specific curricular content (Rogers, Morris, Hook, & Havyer, 2016; Foster, Robb, Cordar, Chaudhary, Noseworthy, & Lok, 2015; DeFries, Rodrigues, Ghorob, & Handley, 2015), but we could not find other examples of medical schools formally soliciting the input of community members regarding curricular objectives.…”
mentioning
confidence: 94%